Beauty in mind: Aesthetic appreciation correlates with perceptual facilitation and attentional amplification - Sarasso, P.; Ronga, I.; Kobau, P.; Bosso, T.; Artusio, I.; Ricci, R.; Neppi-Modona, M. (Neuropsychologia, 2020)
Neuroaesthetic research suggests that aesthetic appreciation results from the interaction between the object perceptual features and the perceiver's sensory processing dynamics. In the present study, we investigated the relationship between aesthetic appreciation and attentional modulation at a behavioural and psychophysiological level. In a first experiment, fifty-eight healthy participants performed a visual search task with abstract stimuli containing more or less natural spatial frequencies and subsequently were asked to give an aesthetic evaluation of the images. The results evidenced that response times were faster for more appreciated stimuli. In a second experiment, we recorded visual evoked potentials (VEPs) during exposure to the same stimuli. The results showed, only for more appreciated images, an enhancement in C1 and N1, P3 and N4 VEP components. Moreover, we found increased attention-related occipital alpha desynchronization for more appreciated images. We interpret these data as indicative of the existence of a correlation between aesthetic appreciation and perceptual processing enhancement, both at a behavioural and at a neurophysiological level. •Abstract pictures with nature-like spatial statistics are more appreciated.•Targets embedded in more appreciated abstract pictures are faster to detect.•Aesthetic judgements correlate with attention-related evoked potential amplitude.•ERP indexes of perceptual learning are enhanced for more appreciated pictures.•Alpha event related desynchronization is increased for more appreciated pictures.